UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KETERLAKSANAAN PEMBELAJARAN JARAK JAUH (PJJ) MELALUI SUPERVISI - Titik Istiqomah (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
This research is motivated by an abnormal situation that is happening around, covid 19 pandemic. This situation causes the system of teaching and learning activities to change, learning is carried out with a distance learning system. This also has an impact on the learning supervision activities carried out by the school head. The purpose of this study was to get a real description on the implementation of distance learning is in SMA Negeri 1 Moga, Pemalang Regency, Central Java Province. This type of research is descriptive qualitative. The time for conducting the research starts from March 2020 to March 2021. The instruments used to get data are from teaching instrument, virtual observations, filling in the online journal, interview and filling in the google form. The population of this study were all teachers of SMA Negeri 1 Moga, totally 58 people. The results obtained from the study were that there were 13 Distance Learning platforms used by teachers, the attendance of students in participating in distance learning was 67%, the curriculum target reached 72% and the learning mastery of students was 58%.